Technology Adaptation in 21st Century Physical Education Learning: Literature Review - Ians Aprilo; Poppy Elisano Arfanda; M. Adam Mappaompo; M. Sahib Saleh; Hasbunallah (Jurnal Dunia Pendidikan, 2023)
The problem that arises is the use of technology in 21st-century physical education learning. Educators are required to use technology in every lesson that is carried out, to the demands and learning outcomes. The purpose of this paper is to present the advantages and disadvantages of technology in physical education learning based on the opinions of several previous studies. The writing of this article is a literature review in nature, analyzing reports that are relevant to the use of technology in learning. Literature was obtained using the search application on Google Scholar, Science Direct, Scopus, Web of Science, and books by entering the keywords "21st-century learning", "technology" and "physical education". The literature sources used are 2013-2023. The results of a review of several articles show that technology can help physical education learning, but some argue that physical education learning cannot be done using technology because the teacher's role cannot be replaced.